NUMERICAL ESTIMATES OF DAILY ENERGY REQUIREMENT AND DAILY CALORIES EXPENDED BY AKUNZA COMMUNITY SCHOOL CHILDREN (FULafia Journal of Science and Technology, 2023)
A research study was carried out using numerical techniques to establish the pattern of daily Estimated Energy Requirement (EER) and Calories Expended (CE) by school children in Akunza community of Lafia in Nasarawa State, Nigeria. Using factors such as age, height, weight, activity level and genetic make-up, the EER and CE per day vary from person to person. In this study, these two variables are estimated for each selected pupil with the use of equations developed by Institute of Medical Equation. The resulting numerical valuesare thereafter interpolated with the use of Lagrange interpolation technique which yielded a set of equations governing the pattern of flow of these variables among the school children in Akunza community. A total of 60 pupils were randomly selected for this study and factors that affect their daily energy expended were measured with specialized instruments (meter rule, digital weighing scale and activity level scale). For the purpose of fast and cost effective assessment of EER and calories burned by each pupil, the set of equations arrived at are inculcated into a computing template. This in essence can be used in estimating energy requirement and calories burned by any member of this population, without subjecting such to any test
Keywords: Age; weight; height; activity factor; calorie; EER; lagrange interpolation